Prediction method of both azeotropic and critical points of the binary refrigerant mixtures - Fedali, Saida; Madani, Hakim; Bougriou, Cherif (Journal of Applied Engineering Science & Technology; Vol 3 No 1 (2017), 2017)
The prediction of the azeotropic point and the determination of the critical point in binary mixtures is very important in refrigerating industry. In this task, a simple method is presented in order to predict and determine both azeotropic and critical points. Our method employs experimental data and a thermodynamic model. 1,1,1,2-tetrafluoroethane (R134a) in the mixture presents the possibility of inventing the azeotropic and critical properties. The mixtures studied in this work are: Cyclopropane (RC270), Propylene (R1270), Hexafluoroethane (R116) and Carbon dioxide (R744) based on 1,1,1,2-tetrafluoroethane (R134a). The model consists of the Peng–Robinson equation of state (EoS), the Mathias–Copeman alph a function and the Wong-Sandler mixing rules involving the NRTL model. The results proved that there is a good agreement between the predicted values and the experimental data. The presented methods are able to predict the azeotropic and determine critical positions.